Current Trends of Creatine Use in Exercise: A Systematic Review - Yücel Makaracı; Kerem Gündüz (Selcuk University, 2021)
Creatine, which is a popular ergogenic aid, is shown among the most effective methods used as performance enhancer in athletes. The aim of this review is to summarize the current publications to show the uses and effects of creatine in exercise. In the present study prepared in a systematic review style, full-text articles about creatine use published in Science Citation Index (SCI), SCI-Expanded and PubMed/MEDLINE databases' journals between 2010 and 2021 were examined. The searching was performed by "creatine", "creatine monohydrate" and "creatine supplementation" keywords. Data from 46 studies showed that creatine loading in individuals who train during high intensity and short term exercise forms affect performance positively, develop muscle mass/strength and increase muscle creatine phosphate (PCr) stores. Moreover, it was found that creatine supplement applied with strength training in elderly individuals increased muscle mass, muscle strength and movement capacity. It is determined that there is no definitive and clear procedure regarding the usage dosage for creatine. Consequently, it has been demonstrated that creatine supplementation is an effective ergogenic aid for the development of muscle and strength for athletes of all levels. In addition, the increase in the number of studies on the creatine usage dosage to be examined in different athlete profiles may lead to a decrease in the contradictions about the usage procedure.